Some Approaches Between Cham, ArbÃ«resh and Arvanitika within the Standard Literary Language - Troplini, Edlira (Richtmann Publishing, 2012)
The regional dialects are not all equally oriented toward the standard language. The orientation towards the prestigelanguage is appropriated to the life of each of the dialects. The more the gap between the standard language (the generalAlbanian) and the provincial dialects, a side or of the Diaspora in general, the greater become the semantic differences, thusincreasing the difficulty in communication. What attracted us most is the pace of change.A considerable weight in developingand changing all linguistic varieties have mainly the extra lingual factors. There are these factors that make some of the dialecthave the development towards general Albanian slower in comparison with other dialects. A typical example of dialects toconsider is the psychological factor as well, which relates to the cause of the displacement of these populations with the samefate, is not the same, but determines them the same. Privilege for such dialect is the fact that they are innovative andconservative at the same time, so there is a convergent relation between the new and the old generations. On the other hand,this relationship is never seen outside the report provincial culture- civic culture, as language itself can not be seen outside thereport language - culture, language - thought. So the starting point for all problems in sociolinguistic perspective is the way thesecommunities are integrated within the host communities.